If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6a + 12b = 6 Solving 6a + 12b = 6 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-12b' to each side of the equation. 6a + 12b + -12b = 6 + -12b Combine like terms: 12b + -12b = 0 6a + 0 = 6 + -12b 6a = 6 + -12b Divide each side by '6'. a = 1 + -2b Simplifying a = 1 + -2b
| -6+7y=15 | | xy-3x-4y+8=0 | | 8-12z=9 | | 5-5(3x-2)=-2(x-8)+38 | | f(-9)=3-4x | | 5e^3x-4=2x | | Px-40=Qx+20 | | X^2+18x+67=O | | 17-4z=17 | | 1.8+2.8x= | | 4/5x-1/2=0 | | 8times-2-3= | | 5/3=12/c | | 28/9=42/s | | 32/25=24/z | | 9=b/q | | 9=b/9 | | 20=b/6 | | 1000=x+0.070x | | 1000=x+0.70x | | 8t-7= | | 8-7=17 | | 3(2y-15)=-(y-6) | | 690+1= | | 20logk=14 | | 8-3m=35 | | 9-m=-3 | | X+Y+Z=36 | | x+9=4(5+2) | | 0.4y-6.7+y-0.3-26y= | | 0.4y-6.7+-0.3-26y= | | 6.4c=0.8 |